Antara Pemilu dan Etika: Batasan Kewenangan Presiden dalam Kontestasi Pemilihan Presiden di Indonesia - Syaiful Bahri; Heri Fathumulloh (Fakultas Hukum Universitas Islam Indonesia, 2024)
Sometimes what is permissible legally may not necessarily be ethical. This is the focal point of scrutiny regarding the actions of the President in involvement in the presidential elections in Indonesia. Where a President essentially holds strong political power relations and can mobilize state machinery, thus when a President supports one of the candidate pairs in the presidential election contest, it raises a question of whether it is ethical within the framework of democratic ethics, even though there is no prohibition for a President to support a candidate pair in Law No. 17 of 2017 concerning Elections. This study uses a normative legal research method with a literature study approach. The methods used are legislative approach and conceptual approach. The results of this study explain that normatively the President has the right to campaign/support a candidate pair, but must comply with provisions, such as taking leave outside state responsibilities and not using state facilities and upholding the principles of democracy, justice, separation of powers, protection of human rights, freedom of the press, and legal compliance. However, ethically, even though permissible in legislation, the President inherently holds power as the Head of State and Head of Government. Therefore, a Head of State must be neutral and embrace all, so it is not ethical if the President supports one of the presidential candidate pairs.